Capillary electrophoresis analysis of different variants of the amyloidogenic protein β2‐microglobulin as a simple tool for misfolding and stability studies. Issue 19 (18th August 2015) - Bertoletti, Laura; Bisceglia, Federica; Colombo, Raffaella; Giorgetti, Sofia; Raimondi, Sara; Mangione, P. Patrizia; De Lorenzi, Ersilia
<x xml:space="preserve">Abstract</x> Free solution capillary electrophoresis with UV detection is here used to retrieve information on the conformational changes of wild‐type β2‐microglobulin and a series of naturally and artificially created variants known to have different stability and amyloidogenic potential. Under nondenaturing conditions, the resolution of at least two folding conformers at equilibrium is obtained and a third species is detected for the less stable isoforms. Partial denaturation by using chaotropic agents such as acetonitrile or trifluoroethanol reveals that the separated peaks are at equilibrium, as the presence of less structured species is either enhanced or induced at the expenses of the native form. Reproducible CE data allow to obtain an interesting semiquantitative correlation between the peak areas observed and the protein stability. Thermal unfolding over the range 25–42°C is induced inside the capillary for the two pathogenic proteins (wtβ2‐microglobulin and D76N variant): the large differences observed upon small temperature variation draw attention on the robustness of analytical methods when dealing with proteins prone to misfolding and aggregation.